Analyzing the Morphology of Late-phase Stellar Flares from G-, K-, and M-type Stars - Denise G. Yudovich; Kai E. Yang; Xudong Sun (The Astrophysical Journal)
Stellar flares occasionally present a peak-bump light-curve morphology, consisting of an initial impulsive phase followed by a gradual late phase. Analyzing this specific morphology can uncover the underlying physics of stellar flare dynamics, particularly the plasma heating–evaporation–condensation process. While previous studies have mainly examined peak-bump occurrences on M dwarfs, this report extends the investigation to G-, K-, and M-type stars. We utilize the flare catalog published by J. Crowley et al., encompassing 12,597 flares, detected by using Transiting Exoplanet Survey Satellite (TESS) observations. Our analysis identifies 10,142 flares with discernible classical and complex morphology, of which 197 (∼1.9%) exhibit the peak-bump feature. We delve into the statistical properties of these TESS late-phase flares, noting that both the amplitude and FWHM durations of both the peaks and bumps show positive correlations across all source-star spectral types, following a power law with indices 0.69 ± 0.09 and 1.0 ± 0.15, respectively. Additionally, a negative correlation between the flare amplitude and the effective temperature of their host stars is observed. Compared to the other flares in our sample, peak-bump flares tend to have larger and longer initial peak amplitudes and FWHM durations and possess energies ranging from 10 ^31 to 10 ^36 erg.